2018
DOI: 10.1016/j.enbuild.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization by local cooling of supercooled sodium acetate trihydrate composites for long-term heat storage

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…After melting and heating SAT in a closed container with smooth inner surfaces to a temperature above 77 °C and by avoiding pressure changes in the container, sensible heat can be discharged until room temperature is reached [28]. Then, the crystallization of the supercooled solution can be initiated by seed crystal injection [29,30] or by local cooling [31], and the heat of fusion will be released as it crystalizes. This heat storage concept dates back to initial research in the late 1920s [32] and was later found to enable more efficient solar heat supply of low-energy buildings in summer and transitional seasons [33].…”
Section: Combined Short and Long-term Heat Storagementioning
confidence: 99%
“…After melting and heating SAT in a closed container with smooth inner surfaces to a temperature above 77 °C and by avoiding pressure changes in the container, sensible heat can be discharged until room temperature is reached [28]. Then, the crystallization of the supercooled solution can be initiated by seed crystal injection [29,30] or by local cooling [31], and the heat of fusion will be released as it crystalizes. This heat storage concept dates back to initial research in the late 1920s [32] and was later found to enable more efficient solar heat supply of low-energy buildings in summer and transitional seasons [33].…”
Section: Combined Short and Long-term Heat Storagementioning
confidence: 99%
“…SAT has a melting point of 58 ºC, relatively high melting enthalpy at 264 kJ/kg (Dannemand et al 2015), and within its operation temperature, density is between 1.25 kg/m 3 and 1.45 kg/m 3 (Dannemand et al 2018). Also, SAT presents stable supercooling, and therefore, generally reliable mechanisms are required for the controlled initialization of crystallization (Englmair et al 2018a).…”
Section: Dhc Systemmentioning
confidence: 99%
“…21 Supercooled phase change materials have found applications as triggerable heat sources in the context of portable hand heating, 22 cold-start automotive engine heating, 23 building-scale air and water heating, 24 and long-term solar energy storage. 25 These applications are mostly intended to raise temperatures in a bulk volume for human comfort or improved device function; accordingly, the spatial and temporal evolution of the thermal profiles produced by triggerable phase change materials have rarely been engineered beyond the shape of the reservoir.…”
Section: Introductionmentioning
confidence: 99%